Gizi Ibu: Fondasi Menyusui dan Masa Depan Anak: Maternal Nutrition: The Foundation of Breastfeeding and Beyond - Basrowi, Ray Wagiu; Darus, Febriansyah; Sundjaya, Tonny; Arumndari, Runi (Amerta Nutrition, 2025)
Background: Breastmilk from a healthy and well-nourished mother serves as the optimal source of nutrition for infant growth and development. The composition of breastmilk is affected by maternal dietary patterns. Beyond its nutritional value, breastfeeding fosters emotional bonding between the mother and infant. Objectives: This study aims to explore the role of maternal nutrition in breastfeeding success and infant’s well-being through scientific and philosophical lenses. Methods: Literature search was conducted via PubMed (Medline Database), including systematic reviews, meta-analyses, and original research articles published within the last decade (2014-2024). The following keywords were utilised: ("maternal nutrition" OR "maternal health" OR "breastfeeding practice" OR "breastmilk") AND ("neurodevelopment" OR "intellectual development" OR "child development"). Inclusion criteria comprised open-access articles, while studies were available only in abstract form were excluded. Discussions: Breastmilk production requires an adequate intake of macronutrients, including protein, carbohydrates, and fats; thus, maternal dietary intake significantly affects breastmilk composition. The nutritional and bioactive components in breastmilk support the infant’s immune function, neurodevelopment, and physical growth, while simultaneously  providing necessary energy for the lactating mother. Breastfeeding should be understood as a holistic practice that extends beyond nutrient transfer, necessitating multisectoral collaboration involving government, non-governmental organizations, healthcare providers, and the population at large. Conclusions: Maternal well-being is intrinsically linked to child health, as well-nourished mothers provide a vital foundation for optimal infant development. A compassionate, community-based approach to maternal nutrition is an essential view that respects individual choices while emphasizing the importance of collective support to enhance the health and well-being of both mother and child.